1984
DOI: 10.3171/jns.1984.60.3.0625
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial extension of inflammatory pseudotumor of the orbit

Abstract: Orbital pseudotumors are inflammatory lesions of the orbit of unknown etiology, which initially mimic an orbital neoplasm. Involvement of the other orbit is uncommon, and extension into the paranasal sinus rare. Intracranial extension of pseudotumor of the orbit is previously unreported. This is a case report of a patient with pseudotumor of the orbit with intracranial extension. The literature of the subject is reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
5

Year Published

1984
1984
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(33 citation statements)
references
References 22 publications
(2 reference statements)
0
28
0
5
Order By: Relevance
“…The inflammatory process within the orbital fat may be localized, and this process can simulate a tumor or may be diffuse within the fatty tissue. The involvement of the lacrimal gland and muscle cone is particularly common (4, 6). …”
Section: Discussionmentioning
confidence: 99%
“…The inflammatory process within the orbital fat may be localized, and this process can simulate a tumor or may be diffuse within the fatty tissue. The involvement of the lacrimal gland and muscle cone is particularly common (4, 6). …”
Section: Discussionmentioning
confidence: 99%
“…11 Another factor that distinguishes ISOI from NSOI is the tendency in some patients to develop aggressive disease. [12][13][14][15][16][17] We had 4 patients with extension of the inflammatory mass into the infratemporal fossa, 3 of whom also had involvement of the pterygopalatine fossa. Another patient had intracranial disease, another showed bone thinning, and another had anterior spread onto the cheek.…”
Section: Commentmentioning
confidence: 99%
“…Typically, there is a temporal sequence of events that demonstrates that the inflammatory process initiates within the orbit and then spills over adjacent structures. Kaye et al 7 and Borruat et al 12 adequately document in their case study that inflammation was originally confined to the orbital contents and extended with time beyond the orbit. In the cases reported by Frohman et al 2 and De Jesús et al, 13 the authors suggested that when more extensive orbital disease was seen compared with the extraorbital inflammation, its origin was probably within the orbit.…”
Section: Discussionmentioning
confidence: 95%
“…4 -7 To date, up to 15 patients with IOI have been reported with intracranial involvement (Table 1). 2,3,[5][6][7][8][9][10][11][12][13] In the vast majority of patients with idiopathic orbital and extraorbital inflammation, the cranial cavity or sinuses are usually involved (Table 1).…”
Section: Discussionmentioning
confidence: 99%